2017
DOI: 10.1007/s13167-017-0117-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of probiotic effects of Lactobacillus and Bifidobacteria strains on cholesterol levels, liver morphology and the gut microbiota in obese mice

Abstract: IMV B-7280 (separately) and a composition of VKL/ VKB/ IMV B-7280 are effective at decreasing the weight of obese mice, decreasing cholesterol level, restoring the liver morphology and beneficially modulating the gut microbiome in high-calorie-induced obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 115 publications
2
52
0
1
Order By: Relevance
“…According to the Food and Agriculture Organization of the United Nations/World Health Organization (FAO/-WHO) definition, probiotics are defined as ''living microorganisms that, when administered in adequate amounts, confer a health benefit on the host.'' 5,6 Probiotics and pro-biotic metabolites have the potential to directly or indirectly adjust the composition of the host intestinal microbiota 7 and activate the endogenous microbial community and regulate the immune system. [8][9][10][11] Currently, the most often used probiotics are lactic acid bacteria (LAB), Bifidobacteria, 7 Propionibacteria, yeasts (Saccharomyces boulardii), and the Gram-negative Escherichia coli strain Nissle 1917.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Food and Agriculture Organization of the United Nations/World Health Organization (FAO/-WHO) definition, probiotics are defined as ''living microorganisms that, when administered in adequate amounts, confer a health benefit on the host.'' 5,6 Probiotics and pro-biotic metabolites have the potential to directly or indirectly adjust the composition of the host intestinal microbiota 7 and activate the endogenous microbial community and regulate the immune system. [8][9][10][11] Currently, the most often used probiotics are lactic acid bacteria (LAB), Bifidobacteria, 7 Propionibacteria, yeasts (Saccharomyces boulardii), and the Gram-negative Escherichia coli strain Nissle 1917.…”
Section: Introductionmentioning
confidence: 99%
“…They are then transformed into secondary bile acids by gut bacteria and reabsorbed by the host. Bifidobacterium is known for its cholesterol lowering properties (Bubnov et al, 2017), which may explain the observed associations. Although it is not directly relevant for the effects of GM corn, this set of data can inform on general aspects of the interface between the gut microbiome and the blood metabolome in laboratory rodents.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota is considered an extension of the self and, together with the genetic makeup, determines the physiology of an organism, metabolism and digestion. Intestinal microbial population largely represented by Bacteroidetes and Firmicutes, has been proven to impact on human health and maintaining homeostasis [4][5][6][7][8][9][10]. The gut microbiota has been recognized as an important contributor to pathological conditions such as obesity and metabolic disorders.…”
Section: Microbiota and Metabolic Syndrome: Strains Stratification Fomentioning
confidence: 99%
“…In the recent study [10] However, the therapeutic use of probiotics and prebiotics treatment and prevention of patients with obesity-related NAFLD is not supported by high-quality clinical studies [170].…”
Section: Liver Disease and Metsmentioning
confidence: 99%
See 1 more Smart Citation